2008
DOI: 10.11646/zootaxa.1674.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Hyphessobrycon rutiliflavidus n. sp., a new characid fish from the upper rio Paraguai, State of Mato Grosso, Brazil (Characiformes: Characidae)

Abstract: Hyphessobrycon rutiliflavidus, new species, is described from the upper rio Paraguai in Cuiab<, State of Mato Grosso, Brazil. The new species differs from all other congeners by the following combination of characters: black humeral spot, slightly diffuse at its tips, and caudal-peduncle blotch present; midlateral body stripe conspicuous in its posteriormost portion, extending to the tips of the middle caudal rays; anal fin with iii,15 to iv,19 rays (mode iv,17); upper jaw length, 42.3 to 49.5% of the head … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
0
4
0
4
Order By: Relevance
“…Some of the aforementioned species were described or mentioned as having two humeral blotches (i.e. H. balbus, H. hamatus, H. moniliger and H. rutiliflavidus) (Moreira et al, 2002a;Bertaco & Malabarba, 2005;Carvalho et al, 2008Carvalho et al, , 2014. The analyses of the type series of H. moniliger revealed that the second humeral blotch described in this species lies in the same position as the first humeral blotch in the remaining species cited.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Some of the aforementioned species were described or mentioned as having two humeral blotches (i.e. H. balbus, H. hamatus, H. moniliger and H. rutiliflavidus) (Moreira et al, 2002a;Bertaco & Malabarba, 2005;Carvalho et al, 2008Carvalho et al, , 2014. The analyses of the type series of H. moniliger revealed that the second humeral blotch described in this species lies in the same position as the first humeral blotch in the remaining species cited.…”
Section: Discussionmentioning
confidence: 95%
“…moniliger and H . rutiliflavidus ) (Moreira et al , 2002 a ; Bertaco & Malabarba, ; Carvalho et al , , ). The analyses of the type series of H .…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that Hyphessobrycon is not monophyletic, but there is no hard evidence to support this assertion (LIMA & COSTA, 2001;LUCENA, 2003;ZARSKE & GÉRY, 2004;BERTACO & MALABARBA, 2005;CARVALHO et al, 2008). Constructing a phylogeny is a daunting task because of the very large number of species in the genus.…”
Section: Discussionmentioning
confidence: 99%
“…As many as possible habitats were explored in each sampling point. The fish specimens were fixed in 10 % formalin and preserved in 70 % alcohol and were identified using pertinent literature and keys (Britski and Garavello 1984;Menezes et al 2003;Britto and Reis 2005;Costa 2006;Lucinda and Costa 2007;Carvalho et al 2008;Lucinda 2008;Oyakawa and Mattox 2009).…”
Section: Methodsmentioning
confidence: 99%